sidrah wrote:

To avoid the complications that can come with the ugly positives and negative signs, wouldn't it be easier to treat this question as an exponentials one?

root of x-squared = change to x-squared to the power of (1/2) = x to the power of (1/2 multiplied by 2) = x to the power of 1.

then bring the denominator up to the numerator:

x in the denominator = x to the power of (-1) in the numerator

SO

now numerator is [x to the power of 1] multiplied by [x to the power of (-1)]

= x to the power of [1 + (-1)]

= x to the power of 0

= 1.

Ans: C

Agree with E

\(sqrt(x^2)= |x|\)

\(e.g sqrt(4) = +2 or -2\)

\(4= 2^2 or (-2)^2\)

\(sqrt(4)=|2|\)

_________________

Your attitude determines your altitude

Smiling wins more friends than frowning